ADAPT: An Algorithm Incorporating PRO‐C3 Accurately Identifies Patients With NAFLD and Advanced Fibrosis. Issue 3 (27th February 2019) - Daniels, Samuel J.; Leeming, Diana J.; Eslam, Mohammed; Hashem, Ahmed M.; Nielsen, Mette J.; Krag, Aleksander; Karsdal, Morten A.; Grove, Jane I.; Neil Guha, Indra; Kawaguchi, Takumi; Torimura, Takuji; McLeod, Duncan; et al.
Abstract : Given the high global prevalence of nonalcoholic fatty liver disease (NAFLD), the need for relevant noninvasive biomarkers and algorithms to accurately stage disease severity is a critical unmet medical need. Identifying those with advanced fibrosis (≥ F3) is the most crucial, as these individuals have the greatest risk of adverse, long‐term, liver‐related outcomes. We aimed to investigate the role of PRO‐C3 (a marker of type III collagen formation) as a biomarker for advanced fibrosis in NAFLD. We measured PRO‐C3 by enzyme‐linked immunosorbent assay in two large independent cohorts with extensive clinical phenotyping and liver biopsy: 150 in the derivation and 281 in the validation cohort. A PRO‐C3‐based fibrosis algorithm that includeda ge, presence ofd ia betes, P RO‐C3, and plat elet count (ADAPT) was developed. PRO‐C3 increased with fibrosis stage (Rho 0.50; P < 0.0001) and was independently associated with advanced fibrosis (odds ratio = 1.05; 95% confidence interval [CI] 1.02‐1.08; P = 0.003). ADAPT showed areas under the receiver operating characteristics curve of 0.86 (95% CI 0.79‐0.91) in the derivation and 0.87 in the validation cohort (95% CI 0.83‐0.91) for advanced fibrosis. This was superior to the existing fibrosis scores, aspartate aminotransferase to platelet ratio index (APRI), FIB‐4, and NAFLD fibrosis score (NFS) in most comparisons. Conclusion: PRO‐C3 is an independent predictor of fibrosis stage in NAFLD. A PRO‐C3‐based score (ADAPT) accurately identifies patients with NAFLD and advanced fibrosis and is superior to APRI, FIB‐4, and NFS.